2015
DOI: 10.1002/masy.201400117
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Surface‐Modified Silica Particles from Rice Husk Ash and Its Composites with Degradable Polylactic Acid

Abstract: A method for preparation of silica particles from rice husk ash (RHA) is developed for use as fillers in an enhancement of gas permeability of polylactic acid (PLA) resin. Silica particles are produced in a one-step process by employing PLA-grafted-chitosan copolymer (PCT) as a polymeric surfactant. Particles with an average size of ca. 30 micron, which are smaller than those obtained from a conventional method, are obtained. The major advantage of this technique is its ease of operation, in which mechanical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Light transmission reduction in both the UV and visible regions is achieved in PLA/modified-silica bio-composite films. As approved by Opaprakasit et al [ 103 ], the films obtained from PLA/modified silica composites have strong potential to be used as biodegradable packaging materials with tunable gas permeability.…”
Section: Potential Applications Of Pla/silica Compositesmentioning
confidence: 99%
“…Light transmission reduction in both the UV and visible regions is achieved in PLA/modified-silica bio-composite films. As approved by Opaprakasit et al [ 103 ], the films obtained from PLA/modified silica composites have strong potential to be used as biodegradable packaging materials with tunable gas permeability.…”
Section: Potential Applications Of Pla/silica Compositesmentioning
confidence: 99%
“…In the last decade, much attention has been focused on polymer composites based on inorganic filler (including silica) [16][17][18] and lignin or cellulose [14,[19][20][21]. Inorganic fillers such as silica are attractive reinforcements that are able to significantly improve thermal, mechanical and also chemical properties of PLA-based biocomposites [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…After milling rice, rice husks are often discarded, landfilled, or burned [45]. To solve this issue of a high amount of residue generation, research incorporating rice husk silica as reinforcement for agricultural fillerreinforced PLA composites has gained significant attention in the literature [14,40,[46][47][48][49][50][51]. Prapruddivongs et al [14] studied the biodegradation behavior of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, introducing commercial SiO 2 in PLA and crosslinked PLA increased the degree and rate of biodegradation. According to Opaprakasit et al [50], PLA/silica composites can improve gas permeability and selectivity. They also reported that the materials had a strong potential to be used as biodegradable packaging films with tunable gas permeability.…”
Section: Introductionmentioning
confidence: 99%